2018
DOI: 10.3390/socsci7050074
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Economic Return of Socioeconomic Status for Black Families

Abstract: Background: According to the Minorities' Diminished Return theory, socioeconomic status (SES) systemically generates larger gains for Whites compared to Blacks. It is, however, unknown whether the effects of baseline SES on future family income also varies between Blacks and Whites. Aims: Using a national sample, this study investigated racial variation in the effects of family SES (i.e., family structure, maternal education, and income) at birth on subsequent household income at age 15. Methods: This 15-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 50 publications
6
48
0
Order By: Relevance
“…Our finding regarding larger effects of history of non-fatal physical assault on risk of mortality in Whites compared to Blacks agrees with other research showing risk and protective factors have stronger effects for Whites than Blacks [20,55], a pattern which is frequently shown for physical and mental health outcomes ( [9,[11][12][13][14][15][16][17][18][19][56][57][58][59][60][61]; see References [20,55] for a review). Stronger effects of low education [17], unemployment [12], poor neighborhood quality [11], depression [16,18,19,62,63], hostility and anger [64], low sense of self efficacy [14], and low perception of control over life [65] were shown for Whites than Blacks.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding regarding larger effects of history of non-fatal physical assault on risk of mortality in Whites compared to Blacks agrees with other research showing risk and protective factors have stronger effects for Whites than Blacks [20,55], a pattern which is frequently shown for physical and mental health outcomes ( [9,[11][12][13][14][15][16][17][18][19][56][57][58][59][60][61]; see References [20,55] for a review). Stronger effects of low education [17], unemployment [12], poor neighborhood quality [11], depression [16,18,19,62,63], hostility and anger [64], low sense of self efficacy [14], and low perception of control over life [65] were shown for Whites than Blacks.…”
Section: Discussionsupporting
confidence: 90%
“…One of the mechanisms of the MDRs is that high education level has a smaller effect on reducing the risk of poverty for AAs, compared to EAs [57,94]. Another mechanism is that high SEP AAs face more not less discrimination [111][112][113][114][115][116][117].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting an economic explanation, empirical research has shown that education generates less income for African Americans than Whites [60,61]. This is also understandable given preferences and practices of labor market and availability of job market and lower quality of education in urban areas [66].…”
Section: Introductionmentioning
confidence: 99%